Thr British civil service: a political excavation and review - Marion David E.
The British political and legal tradition has been no less generous in the guidance it has supplied American practitioners and theoreticians since the founding as it was to the founders themselves.Although perhaps the most notable institutions to draw the attention of students of American politics have been the British parliamentary and party systems, more than a little attention has been devoted to English administrative and civil service practices. Unfortunately, the underlying political thought that informed the English civil service reform movement of the 19th century, and that is still largely responsible for the shape of the modern British administrative service, has been lost from sight. Study of the ref
Keywords: Constitutions -- U.K.; Civil Service -- U.K.